Iron reductases from Pseudomonas aeruginosa. - Cox, C D (1980)
Cell-free extracts of Pseudomonas aeruginosa contain enzyme activities which reduce Fe(III) to Fe(II) when iron is provided in certain chelates, but not when the iron is uncomplexed. Iron reductase activities for two substrates, ferripyochelin and ferric citrate, appear to be separate enzymes because of differences in heat stabilities, in locations in fractions of cell-free extracts, in reductant specificity, and in apparent sizes during gel filtration chromatography. Ferric citrate iron reductase is an extremely labile activity found in the cytoplasmic fraction, and ferripyochelin iron reductase is a more stable activity found in the periplasmic as well as cytoplasmic fraction of extracts. A small amount of activity detectable in the membrane fraction seemed to be loosely associated with the membranes. Although both enzymes have highest activity reduced nicotinamide adenine dinucleotide, reduced glutathione also worked with ferripyochelin iron reductase. In addition, oxygen caused an irreversible loss of a percentage of the ferripyochelin iron reductase following sparge of reaction mixtures, whereas the reductase for ferric citrate was not appreciably affected by oxygen.